An Ultra-Low-Power Human Body Motion Sensor Using Static Electric Field Sensing - Cohn, Gabe; Gupta, Sidhant; Lee, Tien-Jui; Morris, Dan; Smith, Joshua R.; Reynolds, Matthew S.; Tan, Desney; Patel, Shwetak N. (UbiComp '12 Proceedings of the 2012 ACM Conference on Ubiquitous Computing, 2012)
Wearable sensor systems have been used in the ubiquitous computing community and elsewhere for applications such as activity and gesture recognition, health and wellness monitoring, and elder care. Although the power consumption of accelerometers has already been highly optimized, this work introduces a novel sensing approach which lowers the power requirement for motion sensing by orders of magnitude. We present an ultra-low-power method for passively sensing body motion using static electric fields by measuring the voltage at any single location on the body. We present the feasibility of using this sensing approach to infer the amount and type of body motion anywhere on the body and demonstrate an ultra-low-power motion detector used to wake up more power-hungry sensors. The sensing hardware consumes only 3.3 µW, and wake-up detection is done using an additional 3.3 µW (6.6 µW total).
Best Paper Award